A companion to the global Renaissance : English literature and culture in the era of expansion - Singh, Jyotsna G. ([United Kingdom] : John Wiley & Sons, Ltd., Publication, 2013)
This exciting new Companion explores the interactions between Europe and other peoples of both the New and Old worlds during the English Renaissance, and their effect on the literature, culture, art, and history of the period.
Part I : Mapping the global -- Part II : "Contact zones" -- Part III : Networks of exchange : travelling objects -- Part IV : The Globe staged
Includes bibliographical references and index.
Keywords: GREAT BRITAIN -- INTELLECTUAL LIFE -- 16TH CENTURY; GREAT BRITAIN -- INTELLECTUAL LIFE -- 17TH CENTURY; LITERATURE AND SOCIETY